If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + 6x = 12 Reorder the terms: 6x + 10y = 12 Solving 6x + 10y = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10y' to each side of the equation. 6x + 10y + -10y = 12 + -10y Combine like terms: 10y + -10y = 0 6x + 0 = 12 + -10y 6x = 12 + -10y Divide each side by '6'. x = 2 + -1.666666667y Simplifying x = 2 + -1.666666667y
| 2a-7=3a+a+11 | | (40+98+94+102+21+x)/6=88 | | 5+3(s-5t)= | | 19b-9b=35 | | 14v-9b=35 | | 1000+x(10)=2000 | | 3y-2x=3 | | 8.9*10= | | -6x+24=24-9x | | 3(x+2)=32 | | (t-3)2-(t-2)2=5 | | (2x-1)*x=91 | | 70+2m=24m^2 | | 2+a=3(6a-5) | | (2x^2)-4x-30=0 | | (2x-1)x=91 | | r^2+9=6r | | 305+x(5)=350 | | 5x=-37 | | 10=-2x+8 | | 1x+15=25+12x | | -50=19+x | | x+6=-5x+5x | | -7+5=12 | | 6x+42-13x=24 | | x^2+16x+64=-9 | | 7(3x+9)-6(2x+5)= | | 6240000/100= | | 2800+x(150.99)=5819.80 | | -8(2x-4)+7(3+5x)= | | b+3=b*3 | | 6r-6r=-5+r |